Effect of Social Media Function on Student Graduation Rate - Ai Nurhayati; Harya Gusdevi; Angling Sugiatna (Social Science Studies, 2022)
This observation aimed to determine the significant effect of social media facilities on improving the quality of scholars. The research stages began with some interviews with scholars. This observation utilizes the Manova method through the statistic software program. The period to graduate from college and the period of not working is eminently affected by the sort of social media function that student often searches for. This investigation was only conducted on students in Indonesia. This investigation is useful in Indonesia and useful in the fields of social science and industrial engineering.